Expression of the clustered mitochondrial tRNA genes in Saccharomyces cerevisiae: transcription and processing of transcripts. - Palleschi, C (1984)
The transcripts of a cluster of eight tRNA genes localized in the Cap-oxiI region of the mitochondrial genome of Saccharomyces cerevisiae were investigated by hybridization of gene-specific probes on Northern blots of mitochondrial RNA and by S1 mapping of the 5' termini of the transcripts. Two rho- mutants that lack mature tRNA species and accumulate precursors have been used to detect transcripts that are not detectable in wild-type (w.t.) mitochondria. The results have shown the existence of polygenic transcripts carrying at least 5-7 tRNA sequences, both in w.t. and in rho- strains. The existence of several alternative processing pathways, which involve cleavage at the 3' and 5' ends of the tRNA sequences and in the long intergenic regions (possibly at GC clusters), is suggested. Cleavage at the 5' ends of tRNA sequences is defective in the mutant strains. The transcripts of the genes for tRNAThrACN and tRNACys (the tRNA genes immediately downstream from the 21S rRNA gene) have been analyzed; the possibility that these species represent primary transcripts is considered, and potential sites for initiation of transcription of the clustered tRNA genes are discussed.